1998
DOI: 10.1002/(sici)1096-9136(199809)15:9<752::aid-dia678>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Insulin management and metabolic control of Type 1 diabetes mellitus in childhood and adolescence in 18 countries

Abstract: Insulin regimens and metabolic control in children and adolescents with Type 1 diabetes mellitus were evaluated in a cross-sectional, non-population-based investigation, involving 22 paediatric departments, from 18 countries in Europe, Japan, and North America. Blood samples and information were collected from 2873 children from March to August 1995. HbA1c was determined once and analysed centrally (normal range 4.4-6.3%, mean 5.4%). Year of birth, sex, duration of diabetes, height, body weight, number of dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
149
1
9

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 215 publications
(173 citation statements)
references
References 25 publications
14
149
1
9
Order By: Relevance
“…Weight gain is prevalent in adolescent females with type 1 diabetes after attainment of final height (4), which might further impair insulin sensitivity (5). Insulin dosages are often increased to overcome the resistance to insulin, but the metabolic control, however, often deteriorates during the later stages of pubertal development (6).…”
Section: Introductionmentioning
confidence: 62%
“…Weight gain is prevalent in adolescent females with type 1 diabetes after attainment of final height (4), which might further impair insulin sensitivity (5). Insulin dosages are often increased to overcome the resistance to insulin, but the metabolic control, however, often deteriorates during the later stages of pubertal development (6).…”
Section: Introductionmentioning
confidence: 62%
“…This probably reflects an age-related effect; as would be expected, the duration of use tended to increase with age and hence the longest durations were seen in the adolescent group, who also had the highest HbA 1c levels. Several studies have shown that HbA 1c levels in adolescents are typically >8%, and that reduction is often difficult to achieve in this group [5,24]. Indeed there was a negative association between age and number of boluses, and it is likely that missed mealtime boluses in the adolescent age group contributed to this [22].…”
Section: Discussionmentioning
confidence: 98%
“…We investigated the association of circulating CCL3, CCL4, and CCL5 with different definitions of remission and β-cell function in the well characterized prospective Hvidøre cohort of newly diagnosed juvenile type 1 diabetes patients during the first year [11,22].…”
Section: Discussionmentioning
confidence: 99%